Travel time map of Szczecin Main Railway Station - Tomala, Joanna; Pokonieczny, Krzysztof; Mościcka, Albina; Wilbik, Anna (International Conference “Environmental Engineering”, 2017)
This article presents the research on time accessibility of public transport. The study concerned the territory of Szczecin and travelling from anywhere in the city to the Main Railway Station. A self-gathering measurement data method was used, which was developed by Authors in earlier studies. Szczecin was selected as the test area because of the shape of the city as well as the location and shape of the excluded areas (areas not accessible to pedestrians or cyclists). Two travel maps were created, for daytime and nighttime public transportation. The study used 162 measurement points arranged in 1x1 km grids. Travel times to the Main Railway Station were calculated with the use of the jakdojade.pl online service. They were calculated for each measurement point and these values were then interpolated with the IDW method. The travel time maps were evaluated by computing the absolute error on the basis of 10 control points. The absolute error was not greater than 4 minutes, what proves very good accuracy of research. The results of the analysis were compared with the population distribution in Szczecin. The interdependence of population distribution and accessibility of the Main Railway Station was analysed.
Keywords: self-acting method; travel time mapping; IDW method; Szczecin